Нові уявлення про роміщення газоносних пасток баденських відкладів Більче-Волицької зони на площі Слобідка Лісна - Коломия - Заяць, Христина; Субботіна, Наталія; Бєловолова, Людмила; Королюк, Павло; Петришин, Тетяна (НТШ, 2007)
On the basis of available seismic survey data interpretation and geologic-geophysical analysis the structural map of the Bilche-Volytsa zone Pre-Miocene base on the area Slobidka Lisna-Kolomyia from the stand of erosional processes of its development is prepared. The peculiarities of the received paleorelief in comparison with producing wells and gas showings placing are examined. It is noted a connection of gas traps in Badenian deposits with corresponding forms (terraces, definite angle of slopes inclination) of sedimentation basin bottom erosional relief. By the mentioned morphological features of the surface of unconformity prospective areas are predicted, which could have prospecting interest in the inherited forms of Badenian formations.За інтерпретацією сейсмічних матеріялів та аналізом геолого-геофізичної інформації побудована структурна карта доміоценової основи Більче-Волицької зони на площі Слобідка Лісна — Коломия з позиції ерозійних процесів її розвитку. Розглянуто особливості одержаного палеорельєфу у зіставленні з розміщенням продуктивних свердловин та газопроявів. Зазначено приуроченість газоносних пасток у відкладах бадену відповідним формам (терасам, певному куту нахилу схилів) ерозійного рельє- фу дна басейну осадконакопичення. За вказаними морфологічними ознаками поверх- ні неузгодження спрогнозовано перспективні ділянки, які можуть мати пошуковий інтерес в успадкованих формах баденських утворень.
New ideas about gas-Bearing traps distribution in the Bilche-Volytsa one badenian deposits on the area Slobidska Lisna - Kolomyia